Excitation of Whistler Waves Through the Bidirectional Field‐Aligned Electron Beams With Electron Temperature Anisotropy: MMS Observations. Issue 14 (22nd July 2020) - Huang, S. Y.; Xu, S. B.; He, L. H.; Jiang, K.; Yuan, Z. G.; Deng, X. H.; Wei, Y. Y.; Zhang, J.; Zhang, Z. H.
Abstract: Using four‐point measurements from the Magnetospheric Multiscale (MMS) mission, we identify whistler waves at the boundary of an ion scale magnetic hole, which should be locally excited rather than propagated from other regions. Based on the measured local plasma parameters, which include those for bidirectional electron beams with electron temperature anisotropy, the frequency range with the growth rate derived from kinetic theory is consistent with the observations, while the growth rate in the absence of such beams is negative; hence, the observed whistler waves are locally excited by the bidirectional electron beams with electron temperature anisotropy. The dispersion relation, derived from one‐dimensional particle‐in‐cell simulations that are conducted using the inputs of the bidirectional electron beams with electron temperature anisotropy, agrees well with the one from kinetic theory, which further supports this excitation mechanism. Our results shed light on a new excitation mechanism for whistler waves. Plain Language Summary: Whistler waves are nearly field‐aligned propagating and right‐hand polarized electromagnetic modes with the frequency between lower hybrid frequency and electron cyclotron frequency. Whistler waves are frequently and widely detected in the planetary magnetosphere and the interplanetary space and play an important role in the particle dynamics therein. For example, the electrons could be effectively accelerated by the electromagnetic whistler waves. Thanks to the unprecedented high time resolution and multipoint data from the Magnetospheric Multiscale (MMS) mission, the whistler waves are identified at the boundary of a magnetic hole in the magnetosheath. Based on the measured local plasma parameters including bidirectional electron beams with electron temperature anisotropy, both the linear theory based on kinetic plasma and one‐dimensional particle‐in‐cell (PIC) simulations confirm that the observed whistler waves are locally excited by the presence of bidirectional field‐aligned electron beams with electron temperature anisotropy for the first time. Our results shed new light on new excitation mechanism for whistler waves. Key Points: Whistler waves are identified at the boundary of a magnetic hole Linear theory and simulations confirm that whistler waves are excited by bidirectional electron beams with temperature anisotropy Our results shed new light on new excitation mechanism for whistler waves